A numerical solution to math models on the thermal performance of micro flat heat pipes - Evangelista, Emma Mactal (2007)
This study presents a computer program solution to mathematical models of micro flat heat pipes with different grooved wick geometries in predicting their thermal performance. A parallel math model is developed and solved using a numerical program. The model developed is used to thermally characterize micro flat pipes using different wick geometries such as as trapezoidal sinusoidal, rectangular grooves. Thermal characterization involves data generation on the following parameters: axial variation of liquid and vapor pressure drops which determines the necessary capillary pressure needed for continuous operation; axial variation of radius of curvature of liquid-vapor interfacial meniscus which describes the continuous wetting of the wick structure; and variation of maximum heat transport capability with temperature range which describes the effective cooling capacity of the flat heat pipe. Numerical computations are performed for the four wick geometries using two separate working fluids: ammonia and water. The program is validated by comparing the results obtained with existing literature values. This study is a useful tool in design applications for micro flat heat pipes utilizing different groove geometries.
"June 2007"
Thesis (M.S. Chemical Engineering) - University of the Philippines Diliman.
Keywords: Heat pipes -- Mathematical models; Temperature control -- Mathematical models